ARTIFICIAL INTELLIGENCE IN CULTURAL AND ARTS MANAGEMENT: THEMES AND RESEARCH TRENDS - Khalid, Siti Syarina Abdul; Amirrul, Azrul Azizi; Khalid, Muhamad Syukri Abdul; Che Ani, Nurul Safaniza (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Artificial Intelligence (AI) has emerged as an increasingly influential force in the management, production, and governance of arts and cultural sectors, prompting growing scholarly attention across multiple disciplines. However, existing studies remain dispersed and lack a consolidated understanding of how AI is conceptualised and applied within cultural and arts management. This Systematic Literature Review (SLR) aims to map key themes and research trends in the field of Artificial Intelligence in Cultural and Arts Management by synthesising peer-reviewed journal articles published between 2020 and 2025. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, a systematic search was conducted using the keyword combination “Artificial Intelligence and Arts Management” across two major academic databases, namely Web of Science (WoS) and Scopus. Following a structured process of identification, screening, eligibility assessment, and quality appraisal, 27 primary studies were retained for qualitative analysis. The findings were organised through thematic synthesis, resulting in three overarching themes: (1) AI-Enabled Management and Operational Systems in Arts and Cultural Institutions, which highlights the use of AI for organisational planning, decision support, resource optimisation, and audience engagement; (2) AI, Creativity, and Cultural Production, which examines human-AI collaboration in creative processes, curation, valuation, and cultural production practices; and (3) AI, Cultural Policy, Governance, and Societal Implications, which addresses issues related to regulation, cultural labour, participation, ethics, and governance frameworks. The review reveals a dominant trend toward hybrid human-AI models that emphasise augmentation rather than replacement of human expertise, alongside increasing concern for governance, equity, and cultural sustainability. Overall, by consolidating fragmented research and identifying prevailing thematic patterns, this review provides a structured overview of current scholarship. It also highlights emerging directions for future research, practice, and policy development in cultural and arts management.